Severe and Enduring Anorexia Nervosa: Enduring Wrong Assumptions? - Gutiérrez, Emilio; Carrera, Olaia (Frontiers in Psychiatry, 2021)
To the extent that severe and lasting anorexia nervosa (SE-AN) is defined in terms of refractoriness to the best treatments available, it is mandatory to scrutinize the proven effectiveness of the treatments offered to patients. The array of so-called current evidence-based treatments for anorexia nervosa (AN) encompasses the entire spectrum of treatments ranging from specialized brand-type treatments to new treatments adapted to the specific characteristics of people suffering from AN. However, after several randomized control trials, parity in efficacy is the characteristic among these treatments. To further complicate the landscape of effective treatments, this "tie score" extends to the treatment originally conceived as control conditions, or treatment as usual conditions. In retrospection, one can understand that treatments considered to be the best treatments available in the past were unaware of their possible iatrogenic effects. Obviously, the same can be said of the theoretical assumptions underpinning such treatments. In either case, if the definition of chronicity mentioned above is applied, it is clear that the responsibility for the chronicity of the disorder says more about the flagrant inefficacy of the treatments and the defective assumptions underpinning them, than the nature of the disorder itself. A historical analysis traces the emergence of the current concept of ‘typical’ AN and Hilde Bruch’s contribution to it. It is concluded that today’s diagnostic criteria resulting from a long process of acculturation distort rather than capture the essence of the disorder, as well as marginalising and invalidating patients’ perspectives.